Assessing mental resilience with individual and lifestyle determinants among nursing students: An observational study from Greece - Maria Antoniou; Evangelos C. Fradelos; Theano Roumeliotaki; Foteini Malli; Emmanouil, K. Symvoulakis; Dimitrios Papagiannis (AIMS Press, 2024)
The educational environment is important for the development of life skills of nursing students in late- and post-adolescence. Strengthening their mental resilience, enhancing their individual confidence, and controlling stress are necessary conditions in this direction, which will help them cope with the future challenges of their chosen profession. We aimed to study the resilience profiles of nursing students by investigating their mental resilience and its association with their individual characteristics and lifestyle factors. The Connor-Davidson Resilience Scale (CD-RISC-25) scale for resilience, the Perceived Stress Scale (PSS-14) scale for perceived stress, and the Personal Trust and Connection (PerTC) scale for trust and connections were used. The lifestyle determinants were also assessed. An e-survey that targeted 250 nursing students was conducted from November 22 to April 23. Descriptive and advanced statistical analyses were performed. 146 students participated in the study via an on-line questionnaire; the students were predominantly female (82.2%) with mean age of 22 years (SD = 6.8). Two out of ten students smoked (20.5%), 66.4% consumed at least one drink during a usual week, and 48.0% participated in sports during the last year. The mean hours spent on the Internet daily was 4.2 (SD = 1.8) and on social media was 2.7 (SD = 1.6) hours/day. The students scored highly on the 1-to-10 life-satisfaction item (Mean = 6.3, SD = 1.9), where the perceived stress was assessed as moderate/high with a mean of 33 (SD = 4.4) and trust and connections had a mean of 6.2 (SD = 1.1). In the multivariate analysis, the factors found to significantly associate with resilience (CD-RISC-25; Mean = 64.2, SD = 11.8) were age (β = 0.4; 95% CI: 0.1, 0.7), sports participation (β = 5.7; 95% CI: 2.3, 9.1), hours per day spent on social media (β = -1.3; 95% CI: -2.3, -0.3), and the number of friends (β = 0.3; 95% CI: 0.05, 0.5). Finally, resilience was positively associated with life satisfaction and the trust and connections scale (β = 1.8; 95% CI: 0.9, 2.7 and β = 1.8; 95% CI: 0.2, 3.4, respectively).